2017
DOI: 10.1155/2017/7960467
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Coupling of Rhythmical Time Series Using Cross Sample Entropy and Cross Recurrence Quantification Analysis

Abstract: The aim of this investigation was to compare and contrast the use of cross sample entropy (xSE) and cross recurrence quantification analysis (cRQA) measures for the assessment of coupling of rhythmical patterns. Measures were assessed using simulated signals with regular, chaotic, and random fluctuations in frequency, amplitude, and a combination of both. Biological data were studied as models of normal and abnormal locomotor-respiratory coupling. Nine signal types were generated for seven frequency ratios. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 41 publications
5
25
0
Order By: Relevance
“…Persons with abnormal airflow demonstrate a less complex and stronger coupling between breathing and walking compared to healthy controls. 29,30 The results of our study are consistent with previous literature. It was found that patients with COPD used less complex frequency ratios of 1:1 and 3:2; whereas, healthy controls did not use these ratios nearly as often.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Persons with abnormal airflow demonstrate a less complex and stronger coupling between breathing and walking compared to healthy controls. 29,30 The results of our study are consistent with previous literature. It was found that patients with COPD used less complex frequency ratios of 1:1 and 3:2; whereas, healthy controls did not use these ratios nearly as often.…”
Section: Discussionsupporting
confidence: 93%
“…Both breathing and walking should mutually adjust to one another, leading to "compromise between stability and independence." 9,43 Although coupling between breathing and walking may be altered across walking speeds in patients with COPD, 29 the association between energy expenditure and coupling was largely unaffected at slower and faster speeds. Demonstrating that although patients with COPD may choose to walk slower, and in return have a slower respiratory rate, energy expenditure is still increased, partially due to abnormal coupling between breathing and walking.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations